Kebutuhan dan Pemanfaatan Layanan Kesehatan Reproduksi Remaja - Ida Susilaksmi; Zahroh Shaluhiyah; Antono Suryoputro (Jurnal Promosi Kesehatan Indonesia, 2011)
Information and Counseling Center for Reproductive Health Youth (PIK KKR) Adolescent Care and Health Services (PKPR) are not fully utilized by adolescents. This study aimed to find out the description of adolescent reproductive health service utilization in Batang Regency. Data were collected through Focus Group Discussion and in-depth interviews involving 42 people in FGD and 12 insider in-depth interview. Utilization of reproductive health services is still low rod. Most teens have not learned of adolescent reproductive health services in Batang. Some teens perceive the existing services are not innovative, boring and not attractive because the use of inappropriate delivery of media, youth service officer for the clinic is not friendly, discriminate-distinguish and not concern for teenagers. Adolescent reproductive health services needed by adolescents is a service which is located in strategic places, special places, the official collaborationbetween physicians, psychologists, substitute teachers, adolescent, with care official, could keep a secret, do not discriminate and competent. The case of unwanted pregnancy requires special services for psychological therapy and involves active participation of service personnel to conduct home visits.